2020
DOI: 10.3390/v12040414
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between PHB2 and Enterovirus A71 VP1 Induces Autophagy and Affects EV-A71 Infection

Abstract: Enterovirus A71 (EV-A71) is a major pathogen that causes severe and fatal cases of hand-foot-and-mouth disease (HFMD). HFMD caused by EV-A71 seriously endangers children’s health. Although autophagy is an important antiviral defense mechanism, some viruses have evolved strategies to utilize autophagy to promote self-replication. EV-A71 can utilize autophagy vesicles as replication scaffolds, indicating that EV-A71 infection is closely related to its autophagy induction mechanism. VP1, a structural protein of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…Indeed, mAPOL9 interacts with PHB [137] and PHB are present in APOL1 and APOL3 immunoprecipitates ([8] and Uzureau S & Pays E, unpublished). PHB are mainly found in the mitochondrial inner membrane, where they interact with cardiolipin and promote mitochondrial fusion [162], while also behaving as receptors for mitophagy [138] and inducing autophagy upon interaction with some viruses [139] (review in Ref. [163]), all features evoking APOL1 and APOL3 characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, mAPOL9 interacts with PHB [137] and PHB are present in APOL1 and APOL3 immunoprecipitates ([8] and Uzureau S & Pays E, unpublished). PHB are mainly found in the mitochondrial inner membrane, where they interact with cardiolipin and promote mitochondrial fusion [162], while also behaving as receptors for mitophagy [138] and inducing autophagy upon interaction with some viruses [139] (review in Ref. [163]), all features evoking APOL1 and APOL3 characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in macrophages PHB could be involved in the APOL1 restriction of HIV‐1 replication, which results from increased endolysosomal protein degradation resembling autophagy [9]. Conversely, PHB 2 was found to favour infection by Enterovirus A71 through the formation of autophagy vesicles acting as replication scaffolds [139]. Thus, the autophagy‐linked activities of PHB 2 exerted opposed effects on infection by two different picornaviruses, TMEV and Enterovirus A71 [137,139].…”
Section: Apols and Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…NH 4 Cl treatment markedly increases VP0 abundance, indicating that acidification inhibition suppresses the cleavage of capsid protein to generate mature virus [ 62 ]. Prohibitin 2 directs EVA71 infection (intracellular EVA71 RNA and supernatants viral titers) as partially dependent on the acidification of autolysosomes [ 75 ]. However, the question remains of whether acidic vesicles directly affect EVA71 uncoating or maturation or both.…”
Section: The Interplay Between Autophagy and Eva71 Replicationmentioning
confidence: 99%
“…Prohibitin 2, an inner mitochondrial membrane protein from the prohibitin protein family, is a mitophagy receptor mediating mitochondria for autophagic degradation [ 104 ]. A recent study reported that the C-terminus (aa 251–297) of EVA71 VP1 contributes to an increasing LC3-II/LC3-I ratio through interaction with prohibitin 2 [ 75 ], indicating that EVA71 may promote autophagy activity via prohibitin 2. In turn, prohibitin 2 directed EVA71 infection (intracellular EVA71 RNA and supernatants viral titers) in a manner partly dependent on the acidification of autolysosomes, which is involved in the complete autophagy induction [ 75 ].…”
Section: The Interplay Between Autophagy and Eva71 Replicationmentioning
confidence: 99%